2017
DOI: 10.1021/acsami.7b03399
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Ambipolar Organic Field-Effect Transistors by Polymer Preaggregation

Abstract: Ambipolar organic field-effect transistors (OFETs) based on heterojunction active films still suffer from an imbalance in the transport of electrons and holes. This problem is related to an uncontrolled phase separation between the donor and acceptor organic semiconductors in the thin films. In this work, we have developed a concept to improve the phase separation in heterojunction transistors to enhance their ambipolar performance. This concept is based on preaggregation of the donor polymer, in this case pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…Controlling the phase separation of the semiconducting materials (p‐ or n‐type) can generate individual and consecutive migration paths for holes/electrons and thereby result in well controlled ambipolar performance. Janasz et al put forward a novel preaggregation concept by aggregating electron‐donating poly(3‐hexylthiophene) (P3HT) in advance of the solution blend process with electron‐accepting phenyl‐C 61 ‐butyric acid methyl ester (PCBM) . The authors discovered that the fibrillar P3HT aggregates were well dispersed in PCBM matrix and good phase separation was realized owing to the immiscibility between P3HT aggregates and PCBM network, which finally led to prominently increased efficient bipolar mobilities of 0.01 cm 2 V −1 s −1 .…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…Controlling the phase separation of the semiconducting materials (p‐ or n‐type) can generate individual and consecutive migration paths for holes/electrons and thereby result in well controlled ambipolar performance. Janasz et al put forward a novel preaggregation concept by aggregating electron‐donating poly(3‐hexylthiophene) (P3HT) in advance of the solution blend process with electron‐accepting phenyl‐C 61 ‐butyric acid methyl ester (PCBM) . The authors discovered that the fibrillar P3HT aggregates were well dispersed in PCBM matrix and good phase separation was realized owing to the immiscibility between P3HT aggregates and PCBM network, which finally led to prominently increased efficient bipolar mobilities of 0.01 cm 2 V −1 s −1 .…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…In our previous work we reported that hole and electron mobilities were increased by one order of magnitude when P3HT fibrils were surrounded by a PCBM phase. 44 This increase was attributed to the reduction of miscibility between PCBM molecules and P3HT due to the more rigid and ordered polymer structure. TOF SIMS of the P3HT/NDI-C9 surface was performed to confirm if naphthalene molecules penetrated the fibrous network and planar layer of P3HT (Fig.…”
Section: Bilayer Film Structurementioning
confidence: 99%
“…A high-energy barrier prevents the charge carriers from transporting effectively. A very low energy barrier of ~0.1 eV between the work function of m-CNT (4.8 eV) ( 32 ) and the highest occupied molecular orbital energy level of P3HT (~4.9 eV) ( 33 ), as schematically shown in fig. S7B, suggests that such a doped semiconductor can yield high effective carrier mobility.…”
Section: Resultsmentioning
confidence: 99%